American Academy of Audiology Position Statement on Early Identification of Cytomegalovirus in Newborns - Kettler, Maggie; Shoup, Angela; Moats, Shelley; Steuerwald, Wendy; Jones, Sarah; Stiell, Stacy Claycomb; Chappetto, Jenni (Journal of the American Academy of Audiology, 2023)
The American Academy of Audiology recommends early identification of congenital cytomegalovirus (cCMV) through screening to allow for appropriate early diagnosis, intervention, and monitoring for congenital, progressive, and delayed-onset hearing loss in infants with cCMV.Early identification of cCMV is a valuable component in the diagnostic evaluation of infants with sensorineural hearing loss. The Academy recognizes the important role audiologists serve as clinical care providers and educators and advocates for early identification and audiological management of infants with cCMV.
Keywords: CMV; cCMV; congenital; cytomegalovirus; hearing loss; hearing screening; newborn; newborn screening